DEVELOPMENT OF GRANULATED BLAST FURNACE SLAG-BASED GEOPOLYMER COATING FOR METAL SUBSTRATES - RUSILEH, ELLFIRA FANIRA (IRC, 2017)
Metal corrosion is one of the oldest problems in industrial world. Limitations of current coating materials lead researchers to study about green and sustainable material called geopolymer. Geopolymer is an aluminosilicate rich inorganic polymer which has a potential to be a good coating for metal substrates in many corrosive environments. This is due to its excellent properties such as high adhesion strength, fire resistance, acid resistance, thermal resistance and low water permeability. In this project, granulated blast furnace slag (GBFS) geopolymer was synthesized as a coating for mild steel plates by dip coating method. Different formulations of GBFS geopolymer coating were synthesized by varying its water to solid (W/S) and the ratio of sodium silicate solution to sodium hydroxide solution (SS/NaOH). Different percentages of Polycarboxylate-based superplasticizer (SP) were added to see effect of it on properties of geopolymer. Setting time and microstructure of the geopolymers were determined using Vicat apparatus and Scanning Electron Microscope (SEM) respectively. The corrosion rate of coated mild steel plates in corrosive solution were calculated by using weight loss technique. Finally, adhesion strength test using Elcometer 108 according to ASTM D4541 was conducted to see the bonding strength between geopolymer coating and mild steel. From the results obtained, GBFS geopolymer with various SS/NaOH ratio showed longer setting time and less excessive alkali solution. The longest setting time was achieved using GBFS5 with 2% SP which was around 130 minutes. SEM images showed improvement in the microstructure and pore diameter of GBFS1 and GBFS4 with 2% SP addition. GBFS4 with 2% SP could achieved up to 4 MPa of adhesion strength and it showed the lowest corrosion rate of 2.8 um/y after 4 days of immersion in tap water.